9(x-8)-(7-9x)=17x

Simple and best practice solution for 9(x-8)-(7-9x)=17x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-8)-(7-9x)=17x equation:


Simplifying
9(x + -8) + -1(7 + -9x) = 17x

Reorder the terms:
9(-8 + x) + -1(7 + -9x) = 17x
(-8 * 9 + x * 9) + -1(7 + -9x) = 17x
(-72 + 9x) + -1(7 + -9x) = 17x
-72 + 9x + (7 * -1 + -9x * -1) = 17x
-72 + 9x + (-7 + 9x) = 17x

Reorder the terms:
-72 + -7 + 9x + 9x = 17x

Combine like terms: -72 + -7 = -79
-79 + 9x + 9x = 17x

Combine like terms: 9x + 9x = 18x
-79 + 18x = 17x

Solving
-79 + 18x = 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
-79 + 18x + -17x = 17x + -17x

Combine like terms: 18x + -17x = 1x
-79 + 1x = 17x + -17x

Combine like terms: 17x + -17x = 0
-79 + 1x = 0

Add '79' to each side of the equation.
-79 + 79 + 1x = 0 + 79

Combine like terms: -79 + 79 = 0
0 + 1x = 0 + 79
1x = 0 + 79

Combine like terms: 0 + 79 = 79
1x = 79

Divide each side by '1'.
x = 79

Simplifying
x = 79

See similar equations:

| 2(4x-11)=8x-22 | | f(-1)=-4+2 | | 5x+18=15x-22 | | 5x^3+25x^2=0 | | 5+4=2x+17 | | f(x)=x^4-6x+9 | | 5n+10d+25q=180 | | 9(x+3)=9x+15 | | x^4-4x=-1 | | x-7.5=-10.2 | | 48x=64 | | n/7=6 | | 578=474-v | | 3(c+(-7))+(-9)=-45 | | -9-x=15 | | 6b-34=-6b+14 | | 3x-1y=15 | | 0.5*0.52y+2*0.52y+0.3y+1y=900 | | 14-x=-31 | | 0.5*0.52y+2*0.52y+0.3y+1y=0 | | 5d+11e+11d+11e= | | 97-x=256 | | 0.5x+2x+0.3y+1y=0 | | 5+8=23 | | 14x+2=15x-2 | | x(x+1)=146 | | 14-(6-4c)=4c-c | | -2x^2+3=x^2 | | 13x+4=11x+8 | | -10b-4=-2+8b | | 92-6x=21+20 | | 4x+2[3-2(x+5)]=3n-7 |

Equations solver categories